INVENTARISASI GASTROPODA PADA EKOSISTEM MANGROVE DI PERAIRAN PANTAI PAYUMB, KABUPATEN MERAUKE - Sisca Elviana; Bonny Lantang (AGRICOLA, 2016)
The mangrove forest is one of the estuarine ecosystem that is the habitat of a wide variety of animal benthic organisms, one of which is a Gastropod. Macrozoobenthos communities including Gastropods can be used also as an indicator of the recovery of the function of mangrove vegetation, namely by learning community structure Gastropods contained in various stages of mangrove vegetation. The purpose of this study is to inventory the types of Gastropods and community structure in Mangrove ecosystems in the Coastal Waters of Payumb, Merauke. This research was conducted at the coast Payumb, Merauke district in November-December 2015. Year method used is the transect method squares line. Results of research on Payumb waters found Gastropods as 6 Family, 9 Genus and 10 Species and Litorina scraba a Gastropod species with the highest number of individuals.